The Big Triangle Small Triangle Method for the Solution of Nonconvex Facility Location Problems - Drezner, Zvi; Suzuki, Atsuo (Operations research, 2004)
In this paper we propose to modify the big square small square global optimization search in the plane with a big triangle small triangle approach. The triangulation of the feasible region is obtained by using Voronoi diagrams. The resulting algorithm was tested on the obnoxious facility location and the attraction-repulsion Weber problems with excellent results.